Anacroneuria (Plecoptera: Perlidae) from Roncador Mountains, eastern of Mato Grosso state, Brazil - Deprá, Vanessa [UNESP]; De Almeida, Lucas Henrique [UNESP]; Batista, Joana Darc; Da Conceição Bispo, Pitágoras [UNESP] (Taylor & Francis, 2024)
In the present study, specimens of Anacroneuria from the Roncador Mountains, Mato Grosso state, were collected and studied. Eight species were sampled, of which seven represent new records for the state (Anacroneuria corae, A. debilis, A. fittkaui, A. minuta, A. pastaza, A. rondoniae, and A. singularis) and one is a new species that is illustrated and described based in male specimens (Anacroneuria helenae sp. n.). After the contributions of the present study, the total number of species of Anacroneuria recorded for Mato Grosso state increased from four (Anacroneuria dilaticollis, A. jaciara, A. lepida, and A. marlieri) to 12 species. http://www.zoobank.org/urn:lsid:zoobank.org:pub:FE06BD25-E079-4A1A-A1A7-5AB2999CA3F4.
Keywords: aquatic insects; Biodiversity; cerrado; new species